Marxist Idiom In Indian English Poetry: Exploring the Influence of Marxist Idiom in Indian English Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
After  the fall  of  the Berlin  Wall  and the  collapse  of  thebureaucratic Stalinist regimes of Russia and Eastern Europe a wave of euphoriaprovoked in the West. People rejoiced at the demise of Stalinism and termed itas the "end of Socialism."  Thefinal victory of the "free market" was trumpeted from the pages oflearned journals from Tokyo to New York. The strategists of capital wereexultant.  Francis Fukuyama even went sofar as to proclaim the "end of history." Henceforth, the class warwould be no more. Everything would be for the best in the best of allcapitalist worlds. History has proved them incredibly wrong. It we take thePost independence Indian English Poetry in account, we will find that MarxistIdiom has played a crucial role in moulding the literature of Indian in apeculiar way.  Indian English Literatureand especially Indian poetry in English has witnessed multiple social struggleson various levels that motivated a number of poets big and small equally toscribble their pen dipped in the ink of Marxist philosophy of protest. Thepresent paper seeks to explore the unexplored regions of Marxist influence in IndianPoetry in English from its inception to its present day.